Implementing Cost-Effective Policies in the United States to Mitigate Climate Change - Carey, David (OECD Economics Department Working Papers, 2010)
The consensus view of scientists is that the build-up of greenhouse gases (GHG) in the atmosphere is causing global warming. To reduce the probability of severe climate-change impacts and costs occurring, global GHG emissions need to be reduced substantially over coming decades. The United States agreed to a global political agreement to reduce GHG emissions that was acknowledged at Copenhagen (COP15) in December 2009 and negotiations are continuing to work towards binding emissions-reduction commitments by all countries. In view of the scale of emission reductions called for, it is vital that the United States adopt a cost-effective and comprehensive climate change policy. The current Administration is endeavouring to put such a policy package in place. Its core elements are comprehensive pricing of GHG emissions and increased support for the development and deployment of GHG-emissions-reducing technologies. The alternative regulatory approach would be more costly and unlikely to deliver the required scale of reductions in emissions